2013
DOI: 10.1074/jbc.m112.440891
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Biochemical, and Computational Characterization of the Glycoside Hydrolase Family 7 Cellobiohydrolase of the Tree-killing Fungus Heterobasidion irregulare*

Abstract: Background: Family 7 cellulases exhibit significant hydrolytic potential in cellulose degradation. Results: We report the Heterobasidion irregulare GH7 structure and compare it with other GH7 cellobiohydrolases with simulation. Conclusion: H. irregulare Cel7A exhibits intermediate dynamical and structural properties between Phanerochaete chrysosporium Cel7D and Hypocrea jecorina Cel7A. Significance: These results highlight regions of family 7 cellobiohydrolases important for carbohydrate processivity and assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
121
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(130 citation statements)
references
References 61 publications
9
121
0
Order By: Relevance
“…As shown, the HjCel7A loop does not open during the 250-ns MD simulation (44), whereas the LqCel7B exo loop undergoes a conformational change between a closed and open state quite readily on the nanosecond time scale. This difference in exo-loop behavior is likely to increase the propensity of LqCel7B to engage in endotype initiation on the cellulose surface relative to HjCel7A (35), as suggested in previous studies of P. chrysosporium Cel7D and HjCel7A (35,44). Lastly, we note that there are significant protein fluctuations at the product site of LqCel7B not observed in HjCel7A.…”
Section: Resultsmentioning
confidence: 99%
“…As shown, the HjCel7A loop does not open during the 250-ns MD simulation (44), whereas the LqCel7B exo loop undergoes a conformational change between a closed and open state quite readily on the nanosecond time scale. This difference in exo-loop behavior is likely to increase the propensity of LqCel7B to engage in endotype initiation on the cellulose surface relative to HjCel7A (35), as suggested in previous studies of P. chrysosporium Cel7D and HjCel7A (35,44). Lastly, we note that there are significant protein fluctuations at the product site of LqCel7B not observed in HjCel7A.…”
Section: Resultsmentioning
confidence: 99%
“…In Serratia marcescens chitinases, we found that ligand fluctuations and solvation as well as fluctuation of the localized catalytic residues correlated well with previously measured values of apparent processivity between endochitinases and chitobiohydrolases [47]*. In our comparison of the Heterobasidion irregulare Cel7A structure to T. reesei Cel7A and P. chrysosporium Cel7D, we discovered that active site loop regions of the more processive T. reesei Cel7A open and close at a significantly lower rate than the less processive P. chrysosporium Cel7D and putatively less processive H. irregulare Cel7A suggesting the latter two enzymes may perform endo-initiation events more often than T. reesei Cel7A, which can affect processive ability [52]. Each of these studies qualitatively highlighted the potential contributions of enzyme dynamics to processive ability.…”
Section: Thermodynamics Of Cbh Processivitymentioning
confidence: 87%
“…At the same time, the side chain of Asp345 in loop B4 of DdiCel7A and DpuCel7A is suitably positioned for H bonding to OH1 of the glucosyl unit at position ϩ2 of the reducing end. Actually, most GH7 CBHs have aspartate at the corresponding position, but TreCel7A and other Trichoderma species lack this interaction due to a 1-residue deletion in loop B4 (15,50,65).…”
Section: Resultsmentioning
confidence: 99%
“…Glutamine at this position is a rare motif among GH7 CBHs and is found only in another protist, Pseudotrichonympha grassii, a parabasilian symbiont in the gut of termites. A few distantly related basidiomycetes have glutamate at this position; e.g., in HirCel7A, molecular dynamics simulations showed that the glutamate side chain can interact with a bound cellulose chain (15). DpuCel7A and DdiCel7A also possess on the A1 loop two glutamine residues (Q97 and Q99) that would be in direct contact with the cellulose surface when the enzyme is adsorbed (64); TreCel7A possesses only the former of these.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation